Integrated clinical and metabolomic analysis identifies molecular signatures, biomarkers, and therapeutic targets in primary angle closure glaucoma - Kannan, Vishnu; Srimadh Bhagavatham, Sai Krishna; Dandamudi, Rajesh Babu; Kunchala, Haripriya; Challa, Sivateja; Almansour, Abdulrahman I.; Pargaonkar, Ashish; Pulukool, Sujith Kumar; Sharma, Anuj; Sivaramakrishnan, Venketesh (Frontiers in Molecular Biosciences, 2024)
Background: Glaucoma is the leading cause of permanent blindness. Primary angle closure glaucoma (PACG) is diagnosed only after the onset of symptoms resulting in irreversible blindness despite the standard intraocular pressure (IOP) reduction therapy. The identification of potential biomarkers associated with prognosis will help improve disease management. This study aimed to identify mechanisms associated with disease progression, potential biomarkers and therapeutic targets of PACG. Methods: The Clinical data assessment of IOP, cup/disc ratio (CDR) and Retinal Nerve fiber layer (RNFL) thickness of control and PACG group were collected and analyzed for significant differences. The ATP estimation and targeted metabolomic analysis on aqueous humor and cytokine in plasma were performed. The pathways obtained from metabolomics data set was compared with those obtained for data sets from literature. Correlation of clinical parameters were performed with cytokines. Targeted metabolomic analysis of cell culture supernatant from TNFα treated N9 microglia was carried out and overlap analysis was performed with data obtained from PACG patients. Results: Elevated IOP, CDR, ATP, cytokines and reduced RNFL thickness was found in PACG compared to controls. Analysis of PACG and TNFα treated N9 microglial cell culture supernatant shows activation of immunometabolites. The metabolic pathways of PACG, TNFα and ATP treated microglia from the literature show considerable overlap. Biomarker analysis conjured clinical parameters, ATP, cytokines and immunometabolites. Conclusions: This study shows an association of elevated levels of ATP, cytokines, immuno-metabolism and potential microglial inflammation with disease progression rendering them potential biomarkers. P2 receptors, cytokines and IDO1/2 could be potential therapeutic targets.